Neoliberal Europeanisation, Variegated Financialisation: Common but Divergent Economic Trajectories in the Netherlands, United Kingdom and Germany. (21st November 2018) - Ward, Callum; Van Loon, Jannes; Wijburg, Gertjan
Abstract: Revisiting attempts to connect comparative political economy and the geographies of finance, we present a balance sheet analysis of financialisation in the UK, the Netherlands, and Germany from 1992–2012. We define financialisation broadly as a trend towards a greater reliance on assets and/or debt, with particular manifestations across different domains of the economy: a greater reliance on financial tools and metrics for the state and non‐financial corporations, a shift to market‐based banking and increasing dependence on credit or asset‐based welfare for households. We use OECD time‐series balance sheet data and qualitative accounts drawn from the literature to overview economic change in our case countries. Using this informal comparison we develop the concept of 'variegated financialisation' by exploring the common but not convergent financialising trajectories of our case countries and relating them to the politics of finance's institutional embedding.